The Tradition of Ngerampag Traditional Village of Subagan Karangasem Bali in Criminal Law Perspective - Ni Made Liana Dewi (Sociological Jurisprudence Journal, 2021)
In Bali Province, there are various kinds of unique traditions that have been preserved from the past until now, one of which is the Ngerampag Tradition which is found in the Subagan Traditional Village, Karangasem Regency, Bali. However, in its implementation, this tradition has received complaints from some migrant communities who live in the Subagan Adat Village area, because this tradition takes natural products and pets without the knowledge and permission of the owner. The formulation of the problem in this research is how the implementation of the Ngerampag Tradition in the Subagan Traditional Village in the perspective of criminal law and how are the sanctions for people in the Subagan Traditional Village who commit the Ngerampag Tradition whose actions are considered contrary to criminal law in Indonesia. The method used in this research is empirical legal research method, namely a research method through interviews conducted through direct observation. The implementation of the Ngerampag Tradition in the Subagan Traditional Village is basically an activity that violates the law because in its implementation it takes the natural contents of residents other than those mentioned in awig-awig without the permission or the knowledge of the owner. These activities are expressly prohibited in the positive law (KUHP) Articles 362-367 concerning theft. So that in its implementation the Ngerampag Tradition sometimes creates misunderstandings, especially for immigrants who live in the Subagan Village area. However, the problem did not go to court, because the customary village side resolved this problem by means of mediation.